Dicharax (?) candrakirana n. sp. (Gastropoda: Cyclophoridae) from Sempu Island, Indonesia - Nurinsiyah, Ayu Savitri; Hausdorf, Bernhard (Zootaxa, 2017)
The Alycaeinae Blanford, 1864 (Gastropoda: Cyclophoridae) is a species-rich group of caenogastropod land snails distributed mainly in Southeast Asia (Kobelt 1902). The Madagascan endemic Boucardicus Fischer-Piette & Bedoucha, 1965 has also been classified in the Alycaeinae (Emberton 2002). The Asian species of Alycaeinae are characterized by a sutural tube on the last whorl that is closed at its posterior end, but is connected to the outside by radial microtunnels opening near the umbilicus. This device is hypothesized to allow gas exchange when the animal is retracted and the operculum seals the shell aperture (Páll-Gergely et al. 2016).